Design of a communication system for multi-robot manipulator coordination - Lee, Julian Paul Shang Yuan (Nanyang Technological University, 2020)
A tailor-made communication system is necessary for multi-robot-manipulator system to function well. This is because multi-robot-manipulator systems have a different functionality than say, multi-mobile-robot systems. This report aims to detail the building of a communication system designed specifically for a multi-robot-manipulator system. This research was conducted using Zigbee modules, Arduino boards and several types of software. However, this objective was not met due to an unresolved issue. Nonetheless, it was demonstrated that it is possible to configure a single Zigbee communication node.